The effect of future time perspective, emotional intelligence and peer support on career maturity in students - Henie Kurniawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Career maturity is very important for students because it becomes foundation for students after finishing their study. Student career maturity can be influenced by several factors, including future time perspective, emotional intelligence, and peer support. The purpose of this research is to analyze the effect of the future time perspective, emotional intelligence, and peer support either partially or simultaneously on career maturity. The type of this research was quantitative research. The type of quantitative research used in this research is causal comparative research. The sample of this research were 110 students of Professor Kiai Haji Saifuddin Zuhri State Islamic University Purwokerto taken using convenience sampling technique. The instruments used in this research are Carstensen and Lang Future Time Perspective scale (CL-FTP), Emotional Intelligence Scale referring to the aspects proposed by Salovey, social support scale proposed by Sarafino, and career maturity scale using career maturity dimension from Rehfuss & Sickinger. The data analysis used multiple linear regression testThe result of this research concludes that the future time perspective and emotional intelligence partially affect career maturity. Peer support partially has no effect on career maturity. Career maturity is a continuous process influenced by several variables and students need careful preparation and career planningOn the other hand, the combination of future time perspective, emotional intelligence, and peer supporteffect career maturity.